Supercooling points of freeze-avoiding bumble bees vary with caste and queen life stage. (February 2022) - Keaveny, Ellen C.; Waybright, Sarah A.; Rusch, Travis W.; Dillon, Michael E.
Abstract: Bumble bees thrive in cold climates including high latitude and high altitude regions around the world, yet cold tolerance strategies are largely unknown for most species. To determine bumble bee cold tolerance strategy, we exposed bumble bees to a range of low temperatures and measured survival 72 h post-exposure. All bees that froze died within 72 h while only one bee died without freezing, suggesting that bumble bees are generally freeze-avoiding insects and may be slightly chill susceptible. We then assessed whether temperatures that cause internal ice formation (supercooling points, SCP) varied among bumble bee castes (drones, workers, and queens), or across queen life stages, collection elevation, species, or season. Males froze at significantly lower temperatures than workers or queens. Queens in pre-overwintering or overwintering states froze at significantly lower temperatures than queens stimulated to initiate ovary development by CO2 narcosis (i.e., "spring" queens). We also tested whether the presence of water (i.e., wet or dry) or ramping rate affected SCP. As expected, queens inoculated with water froze at significantly higher temperatures than dry queens. SCP tended to be lower, but not significantly so, at faster ramping rates (0.5 °C/min vs 0.25 °C/min). We also found no differences in SCP between queen bumble bees collected in spring and fall, between queens collected at two sites differing in elevation by 1100 m, or between three field-caught bumble bee species. Bumble bees appear to have relatively high, invariable SCPs, likely making them highly susceptible to freezing across all seasons. As bumble bees are not freeze-tolerant and appear to lack the ability to prevent freezing at temperatures much below 0 °C, they may rely on season- and caste-specific micro-habitat selection to thrive in cold climates. Highlights: Bumble bees are freeze avoidant. Male bumble bees are more cold tolerant than females. Queens are most freeze tolerant just prior to and during overwintering. Bumble bees may rely on micro-habitat selection to thrive in cold climates.